EFEKTIFITAS PELATIHAN DALAM MENINGKATKAN PENGETAHUAN DAN KETERAMPILAN BATUAN HIDUP DASAR PADA ORANG AWAM. - Abdul Qodir (LPPMK STIKES Widyagama Husada, 2020)
Out-of-hospital cardiac arrest (OHCA) is a major health problem throughout the world. The best survival rates are achieved when trained people provide OHCA victims with basic life support (CPR). This study aims to evaluate the effectiveness of training on improving knowledge and skills basic life support in lay people. One group pretes posttest design was conducted in this study in integrated laboratory Widyagama Husada School of health. A total 15 participants were ware selected by Consecutive Sampling. Data were collected on respondent characteristics, knowledge and practical skills basic life support. Data were analyzed using paired t-tests. The mean score in knowledge and skills ware 54,67 and 33,67 at pretest and 76,3 and 85,07 (p = 0.000) at posttest. The Training significant on improving Knowledge and Skills Basic Life support in Lay People.